The wind in the willows - Grahame, Kenneth, 1859-1932.; Smallman, Steven (New York : Scholastic, 1988)
The escapades of four animal friends who live along a river in the English countryside--Toad, Mole, Rat, and Badger.
Subtitle from cover: A story of loyalty and friendship.
"Apple paperback."
Originally published 1908 with different illustrator.
Large print.
Keywords: Animals -- Juvenile fiction; Friendship -- Juvenile fiction; England -- Juvenile fiction